An effective natural mineral-catalyzed heterogeneous electro-Fenton method for degradation of an antineoplastic drug: Modeling by a neural network - Hajiahmadi, Mahsa; Zarei, Mahmoud; Khataee, Alireza (Pergamon-Elsevier Science Ltd, 2022)
In this study, the heterogeneous electro-Fenton method was used to remove Paclitaxel as an antineoplastic medicine. The cathode based on three-dimensional graphene (3DG) was applied as a gas diffusion electrode. The potential of five eco-friendly and recyclable iron minerals derived from nature (Magnetite, Siderite, Hematite, Limonite, and Pyrite) was investigated. Among the applied iron minerals, Pyrite showed the best, and Magnetite and Siderite showed good catalytic activity at pH 3.0. The current intensity of 300 mA, pHi 7.0, Paclitaxel concentration of 3 mg L-1, amount of Pyrite 4.5 g L-1, and time of 120 min was the optimum condition of the process with the removal efficiency of 99.13% in the presence of Pyrite. Repeating the experiments eight times revealed the reusability of the prepared 3DG as a cathode. Also, using radical scavengers indicated the principal role of the hydroxyl radicals (center dot OH) in the treatment process. Analysis of total organic carbon reached 77.64% mineralization of 3 mg L-1 Paclitaxel at 360 min. Finally, ten by-products of small molecules were identified by gas chromatography-mass spectrometry device.
Keywords: Advanced oxidation process; Heterogeneous electro-fenton; Iron mineral; Anticancer drug; Paclitaxel; Artificial neural network